Faith-Based Economic Empowerment: The Role of Islamic Religious Extension Workers in Community Development in Padangsidimpuan City, North Sumatra, Indonesia - Dianto, Icol; Zilfaroni, Zilfaroni (Islamic Management and Empowerment Journal, 2026)
This article examines the role of Islamic religious extension workers in the economic empowerment of Taklim Council communities in Padangsidimpuan City and its implications for debates on religion, empowerment, and community development. Using a qualitative field-study approach, data were collected through participatory observation and semi-structured interviews with religious extension workers, institutional officials, and Taklim Council administrators and members. Data were analyzed thematically using the Miles and Huberman model, while validity was ensured through source and method triangulation. The findings reveal that religious extension workers act as moral brokers, social facilitators, and institutional mediators in community-based economic empowerment. Empowerment is understood not only as income improvement but also as strengthening collective capacity, social trust, and moral legitimacy toward productive economic activities. However, these roles remain constrained by bureaucratic dependence, limited resources, and weak integration with the local economic ecosystem. This study highlights the strategic contribution of religious actors in sustainable community empowerment practices.